2000
DOI: 10.18060/20
|View full text |Cite
|
Sign up to set email alerts
|

Faculty-Student Collaboration: Issues and Recommendations

Abstract: F Fa ac cu ul lt ty y--S St tu ud de en nt t C Co ol ll la ab bo or ra at ti io on n: : I Is ss su ue es s a an nd d R Re ec co om mm me en nd da at ti io on ns sAbstract: This exploratory qualitative study of 11 social work faculty identified the benefits and risks of faculty-student collaboration. Benefits articulated include helping students learn to write for publication, learning the publication process, getting innovative student material published, and enriching the project through shared problem-solvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…It was critical for the student to be involved in the authorship of the paper as a means to offer mentorship and continued learning and development through the writing and reflective process (Barretta-Herman and Garrett, 2000;Wegener and Tanggaard, 2013); to be consistent with feminist values of interrupting problematic hierarchical relationships specifically in relation to claiming ownership over knowledge (Moss et al, 1999); and because, simply, this paper could not be written and would not exist in the absence of either author.…”
Section: Methodsmentioning
confidence: 99%
“…It was critical for the student to be involved in the authorship of the paper as a means to offer mentorship and continued learning and development through the writing and reflective process (Barretta-Herman and Garrett, 2000;Wegener and Tanggaard, 2013); to be consistent with feminist values of interrupting problematic hierarchical relationships specifically in relation to claiming ownership over knowledge (Moss et al, 1999); and because, simply, this paper could not be written and would not exist in the absence of either author.…”
Section: Methodsmentioning
confidence: 99%
“…Deciding author order is one of the major ethical considerations for collaborate student research (Barretta-Herman & Garrett, 2000;Mauer, 2017). The class agreed to author order based on amount of work contributed, including the instructor.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…25,26 An early, exploratory study of social work faculty identified several key benefits, as well as risks of faculty-student collaboration, such as situations where the student performs all or most of the work but receives little to no credit. 27 In an effort to reduce risks, Barretta-Herman and Garrett 27 suggest that faculty-student collaborators utilize written agreements clarify expectations. Heckel and Moore 28 note key considerations such as the primacy of student interest and self-direction, the need for clarity about the student-faculty partnership and roles, and the importance of communication and flexibility throughout the process.…”
Section: • Collaborative Research: Benefits and Challengesmentioning
confidence: 99%